mRNA expression of SMPD1 encoding acid sphingomyelinase decreases upon antidepressant treatment - Rhein, Cosima; Zoicas, Iulia; Marx, Lena M.; Zeitler, Stefanie; Hepp, Tobias; von Zimmermann, Claudia; Mühle, Christiane; Richter-Schmidinger, Tanja; Lenz, Bernd; Erim, Yesim; Reichel, Martin; Gulbins, Erich; et al. (International Journal of Molecular Sciences, 2021)
Major depressive disorder (MDD) is a severe psychiatric condition with key symptoms of low mood and lack of motivation, joy, and pleasure. Recently, the acid sphingomyelinase (ASM)/ceramide system has been implicated in the pathogenesis of MDD. ASM is a lysosomal glycoprotein that catalyzes the hydrolysis of sphingomyelin, an abundant component of membranes, into the bioactive sphingolipid ceramide, which impacts signaling pathways. ASM activity is inhibited by several common antidepressant drugs. Human and murine studies have confirmed that increased ASM activity and ceramide levels are correlated with MDD. To define a molecular marker for treatment monitoring, we investigated the mRNA expression of SMPD1, which encodes ASM, in primary cell culture models, a mouse study, and a human study with untreated MDD patients before and after antidepressive treatment. Our cell culture study showed that a common antidepressant inhibited ASM activity at the enzymatic level and also at the transcriptional level. In a genetically modified mouse line with depressive-like behavior, Smpd1 mRNA expression in dorsal hippocampal tissue was significantly decreased after treatment with a common antidepressant. The large human study showed that SMPD1 mRNA expression in untreated MDD patients decreased significantly after antidepressive treatment. This translational study shows that SMPD1 mRNA expression could serve as a molecular marker for treatment and adherence monitoring of MDD.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Acid sphingomyelinase; Amitripty-line; Antidepressants; Biomarker; FIASMA; Fluoxetine; Major depressive disorder; SMPD1